Meta-analysis of empirical evidence on the labour market impacts of immigration - Simonetta Longhi; Peter Nijkamp; Jacques Poot (Institute for the Study of Labor (IZA), 2008)
The increasing proportion of immigrants in the population of many countries has raised concerns about the 'absorption capacity' of the labour market, and fuelled extensive empirical research in countries that attract migrants. In previous papers we synthesized the conclusions of this empirical literature by means of meta-analyses of the impact of immigration on wages and employment of native-born workers. While we have shown that the labour market impacts in terms of wages and employment are rather small, the sample of studies available to generate comparable effect sizes was severely limited by the heterogeneity in study approaches. In the present paper, we take an encompassing approach and consider a broad range of labour market outcomes: wages, employment, unemployment and labour force participation. We compare 45 primary studies published between 1982 and 2007 for a total of 1,572 effect sizes. We trichotomise the various labour market outcomes as benefiting, harming or not affecting the native born, and use an ordered probit model to assess the relationship between this observed impact and key study characteristics such as type of country, methodology, period of investigation and type of migrant.
urn:nbn:de:101:1-2008040134
Keywords: C51; 330; Immigration; labour market; factor substitution; comparative research; meta-analysis; Einwanderung; Beschäftigungseffekt; Faktorsubstitution; Lohnniveau; Arbeitsmarkt; Schätzung; Neuseeland